2002
DOI: 10.1074/jbc.m108804200
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Effects Potentiating the Release of the Second Fibrinopeptide A from Fibrinogen by Thrombin

Abstract: Fibrin formation depends on the release of the two N-terminal fibrinopeptides A (FPA) from fibrinogen, and its formation is accompanied by an intermediate, ␣-profibrin, which lacks only one of the FPA. In this study, we confirm that the maximal levels of ␣-profibrin found over the course of thrombin reactions with human fibrinogen are only half of what would be expected if the first and second FPA were being released independently with equal rate constants. The rapidity of release of the fibrinopeptides by thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…This method requires the presence of GPRP-NH 2 in the thrombin-containing reaction mixture. 52 We found that the overall rate of fibrinopeptide release was inversely proportional to the concentration of GPRP-NH 2 , and its presence slowed the rate of peptide release from both fibrinogens. We carried out several ␣-profibrin generation experiments at concentrations of GPRP-NH 2 ranging from 4 to 12 mM, and in every case we observed that ␣-profibrin generation was slower from fibrinogen 2 than from fibrinogen 1.…”
Section: Thrombin-mediated Fibrin Formationmentioning
confidence: 86%
See 2 more Smart Citations
“…This method requires the presence of GPRP-NH 2 in the thrombin-containing reaction mixture. 52 We found that the overall rate of fibrinopeptide release was inversely proportional to the concentration of GPRP-NH 2 , and its presence slowed the rate of peptide release from both fibrinogens. We carried out several ␣-profibrin generation experiments at concentrations of GPRP-NH 2 ranging from 4 to 12 mM, and in every case we observed that ␣-profibrin generation was slower from fibrinogen 2 than from fibrinogen 1.…”
Section: Thrombin-mediated Fibrin Formationmentioning
confidence: 86%
“…[50][51][52] GPRphoresis uses electrophoresis to cause the countermigration of Gly-pro-arg-pro amide (GPRP-NH 2 ; Bachem Biosciences, King of Prussia, PA) in GPRP-NH 2 -impregnated gels to separate GPRP-NH 2 -insoluble fibrin monomers lacking both FPAs (␣-fibrin) from a fibrin intermediate termed ␣-profibrin lacking only one FPA, and it is soluble in buffer solutions lacking GPRP-NH 2 . After electrophoresis, the band containing ␣-profibrin comigrates with fibrinogen and is distinguished from it by immunoprobing the gel with an anti-fibrin ␣17-23 antibody (Roche Diagnostics, Basel, Switzerland) that reacts with ␣-fibrin or ␣-profibin but not with fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue transglutaminase (tTG), a single-chain enzyme that is widely distributed in cells and tissues, does not require activation by proteolysis. The substrate specificity of FXIIIa for ␤-casein, fibrin/fibrinogen, or their peptide derivatives differs from that of tTG (7)(8)(9). Among the plasma proteins that have Gln substrate site(s) for FXIIIa, ␣ 2 AP is recognized as having the highest kinetic efficiency (k cat /K m(app) ), with its substrate site being the second Gln from the N terminus (10,11).…”
mentioning
confidence: 99%
“…Under forced conditions, however, similar ␥⅐␥ and A␣ n crosslinking can also be achieved with fibrinogen. In contrast, TG reacts quite readily with fibrinogen in the soluble phase, generating A␣ p ⅐␥ q type of crosslinked, intermolecular chain combinations (8,9) as well as A␣⅐␥ crosslinking within the monomeric fibrinogen units:…”
mentioning
confidence: 99%